Spatial–temporal characterization of droughts in Angola - Mateus, Nelson P. A. [UNESP]; Marengo, José A.; Cunha, Ana P. M.A.; Diogo, Anacleto Marito; António, Jaime Fernando (Wiley, 2024)
This study presents a scientific study conducted in Angola, focusing on the impact and characteristics of drought events in the country. The research endeavours to assess the primary climatic conditions linked to drought events within Angola, including an investigation into their spatiotemporal patterns. To achieve this, an evaluation of drought events’ frequency, duration and intensity has been carried out employing the Standardized Precipitation Index (SPI). Furthermore, the extent of affected regions has been determined using the Integrated Drought Index (IDI). For this, the frequency, duration and intensity of drought events are evaluated using the Standardized Precipitation Index (SPI). The assessment of the affected areas was carried out using the Integrated Drought Index (IDI). The results showed that Angola was repeatedly affected by drought events. The longest drought events were identified in the South and Center regions of the country. In the South region, the longest drought occurred from 1992 to 1997, totaling 83 consecutive months of drought in the region, in the Center the longest event occurred during the years 1994 to 1997, and in the North region between 2003 and 2005, totaling 46 and 23 months, respectively. The climatic conditions evaluated for the drought events studied (1989/1990, 1994/1995, 2014/2015 and 2018/2019) showed that most drought events in the country are associated with the variation of sea surface temperatures in the South Atlantic Ocean. The analysis of the drought category showed that during the years analysed, about 29.7% of the territorial extension of Angola were affected by drought events in the severe to exceptional category.
Keywords: Angola; climate; drought